Situating the subject: gender and entrepreneurship in international contexts - Ashe, Fidelma; Treanor, Lorna (International journal of gender and entrepreneurship, 2011)
Purpose - The purpose of this paper is to offer a perspective to further the understanding of gender entrepreneurship. This paper considers the situatedness of the gendered entrepreneur within diverse international contexts marked by different constitutions of gender identities and networks of power, both within the context of contributions within this special issue but also more broadly within the field of gender and entrepreneurship research.Design methodology approach - The authors adopt a feminist perspective and analyse the different framings of identity within gender and entrepreneurship literature and their contributions to our understandings of the concepts of both power and gendered identities.Findings - The paper finds that power and identity are configured in different contexts in ways that open arenas for future analysis.Originality value - The paper highlights the importance of considering masculinities within gender and entrepreneurship research offering support for further analyses of entrepreneurial masculinities by examining two studies that expose entrepreneurial masculinities as shifting subjectivities influenced by men's social power, but also by interactions between men and women and broader cultural contexts and transitions. In so doing, it contributes to the research agenda in relation to gender and entrepreneurship in different contexts.